Demographic and etiological analysis of peripheral vertigo, as a common public health problem - Mehar, Hemant; Bhandari, Pranay; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Vertigo was defined by Gowers in 1893 as any movement or sense of movement either in the individual himself or in external environment that involves a defect, real or seeming in the equilibrium of body. The aim of present study was evaluation of demographics and etiology of patient presenting with vertigo. Methods: The study was prospective study. Present study consisted of an assessment of 55 cases of vertigo whose examination was conducted in the ENT department. All patients were evaluated for the various causes of vertigo and include all the age group and both sexes. Results: Out of 55 patients, 80% belonged to 21-50 years age group. In present study, 29 cases out of 55 cases were diagnosed as a case of BPPV. Among them 22 diagnosed as posterior canal BPPV (benign paroxysmal positional vertigo) and 7 as horizontal canal BPPV. Conclusions: The maximum number of patients belongs in the 4 decades. Of the associated sign and symptoms dizziness is most common than dizziness with other sign and symptoms. Among peripheral causes posterior canal BPPV is most common. This approach leads not only to diagnosis but also helps to plan the intervention for the patient. In the present study, 12 cases (21.8%) were diagnosed clinically normal. It shows those tests used in this study are efficient to diagnose true or false vertigo.